Land Distribution and Financial System Development - Vollrath, Dietrich; Erickson, Lennart (Washington, D.C. : International Monetary Fund, 2007)
Research on credit markets from developing economies, as well as work on the origin of institutions in general, has suggested that land inequality may play a role in determining financial development. In this paper we establish empirically that initial land inequality is a significant predictor of financial depth across countries, even while controlling for other predictors such as legal origin, ethnic fractionalization, and income inequality. To examine this relationship we have created a new measure of land distribution within countries that builds upon the work of Deininger and Squire (1998) by explicitly accounting for landlessness. In addition to being a significant predictor of financial development, land inequality is found to be uncorrelated with other fundamental characteristics of economies, suggesting its possible use in a wider range of research.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet